PATIENT SAFETY AND CLINICAL RISK MANAGEMENT - WHERE DO WE STAND? - Sheikh, Muhammad Iqbal; Wajid, Gohar (Journal of Ayub Medical College Abbottabad, 2004)
Modern healthcare has undoubtedly extended extreme benefits to human beings, and yet is not completely free from clinical adverse incidents. The complex interaction of technologies, processes and human interface makes clinical practice a risky affair, inevitably prone to adverse events and accidents. The issue of adverse events in healthcare is not new but has gained increasing attention of policy makers, health managers and clinicians in recent years. A study conducted by Schimmel1 on adverse events as early as 1964 reported the rate of adverse events as 19.2 percent with associated mortality of 1.3 percent. Other studies on the same subject include California Medical Association Study2, Standford Centre for Health Care Research3 and a relative recent study done by Brennan et al. (adverse events 3.7 percent and associated mortality 13.6 percent).4 The extent of problem became fully obvious with publication of series of reports from around the world during 90’s. The studies carried out in the US, Europe, Australia and New Zealand concluded that the scale of this problem was much bigger than originally thought and nearly 4-10 percent of all patients admitted to hospitals were harmed, some temporarily and others permanently. These studies also drew attention to avoidable events that could be prevented and the financial and human cost of these events.5 It is such events (or their root causes) where risk management efforts are currently focused. Clinical risk is defined as "the potential for an event, action or interaction (or lack of them) thereby leading to patient harm or adversely affecting patient outcome." Examples of risks include: medication and diagnostic errors, unexpected deaths, poor surgical outcome, medical equipment failure, breaches of confidentiality; etc. Clinical Risk Management is a systematic way of identifying, assessing controlling and monitoring risks. The risk assessment framework is designed to help identify the varied causes of latent failure, inadequate or inappropriate defences, and active human failure.6 Risk management works best where strategies are designed to minimize risks both in the delivery of health care and the environment in which care is provided. One cannot expect clinicians to perform in an optimal manner if the conditions around them are less than optimal. Risk management is now considered fundamental to patient care and an important component of quality management. In UK, Risk Management has been placed at the heart of Corporate and Clinical Governance over the past few years.7,8 Some of the high-risk industries such as aviation, nuclear and petro-chemical industries have been commercially driven to learn from experience, whereas health services are often rewarded for their errors through the payment of rework to rectify poor patient outcome. In many countries, financial indicators are often used to measure healthcare performance. This may explain why ’˜safety’ is not a primary objective within most strategic plans and why most healthcare providers are neither directed to nor accountable for improving safety of the healthcare system. As most of the organizational management systems focus on financial performance, the ethical requirement to improve safety is often left to individual clinicians. However, individual clinicians are rarely empowered and often not trained to effect system-wide improvements. Ethical and or legal requirements for safety either do not exist or are usually in very primitive form in most of the healthcare systems, especially in developing countries. Safety is mostly restricted to fire safety or occupational safety. Patient safety is not even considered as an issue. In the absence of well-structured Quality Improvement programs, a large number of hospital incidents are never reported or investigated. At the best, when investigations are carried out they only focus on individuals, rather than the environment or systems in which they operate. There is a need beyond any doubt that Pakistani healthcare system needs to be assessed thoroughly from safety perspective. If the findings from international studies are implied to Pakistani healthcare system, the number of patients suffering from adverse events must be in millions with tens of thousands of deaths due to medical errors alone, causing huge financial loss and social trauma to individuals, families and the healthcare system who ultimately bear the brunt of those errors made by qualified as well as non-qualified practitioners. Applying Risk Management to Pakistani healthcare system may not be an easy task; where the system has never been a political priority, vision for quality is lacking, policies are often non existent, decisions are made on ad-hoc basis and health services management infrastructure is not built on scientific grounds. Perhaps the biggest flaw in the system is that it is still ’˜physician centred’, and the patient has often no say and no choice. Developing strategies to safeguarding patients and decreasing iatrogenic injury is indeed challenging and yet equally rewarding. To achieve this in the Pakistani healthcare system, strong political will, effective organisational leadership and robust structures and processes will be required. A high level of safety awareness needs to be created amongst all sections of population, politicians, clinicians and users of healthcare alike. It is hoped that this would provide an impetus for change; a change where working of clinicians and hospital systems would become transparent and where a strong ethos of public service and accountability exists. At practical level, a good start would be to include patient safety in the under and postgraduate training programmes of all clinicians; doctors, dentists, nurses and other healthcare staff. The Government must develop a robust regulatory environment for all health professionals as well as legal framework for compensating patients who suffer in hands of poorly performing clinicians. As humans, clinicians are prone to make mistakes and about honest mistakes, prophet Muhammad (SAW) said, Allah forgives acts committed by in error, or under coercion; and forgetfulness.9 Indeed, the distinction between honest mistakes and wilful neglect is maintained by Muslim jurists yet there is no wrong action in committing an error; but in all cases the damage is to be redressed.10